Disclosure of Sexual Victimization: Effects of Invalidation and Shame on Re-Disclosure - Catton, Ashley K. H.; Dorahy, Martin J.; Yogeeswaran, Kumar (Journal of interpersonal violence, 2023)
Research on disclosure of sexual victimization has consistently demonstrated that the act of disclosure and the disclosure recipient have a synergistic effect in facilitating either positive or negative post-assault outcomes. While negative judgments such as victim blame have been argued to serve a silencing function, experimental investigations of this claim are lacking. The current study investigated whether invalidating feedback in response to self-disclosure of a personally distressing event produced feelings of shame, and whether shame influenced subsequent decisions around re-disclosure. Feedback type (validating, invalidating, no feedback) was manipulated in a sample of 142 college students. Results partially supported the hypothesis that shame resulted from invalidation, however shame was better predicted by individual perceptions of invalidation than the experimental manipulation. Although few participants opted to make changes to the content of their narrative for re-disclosure, those who did had higher levels of state shame. Results suggest that shame may be the affective mechanism by which invalidating judgments silence victims of sexual violence. The present study also supports the distinction previously made between Restore and Protect motivations in managing this shame. This study provides experimental support for the notion that an aversion to being shamed, communicated via an individual’s perception of emotional invalidation, features in judgments of re-disclosure. Perceptions of invalidation, however, vary individually. Professionals working with victims of sexual violence should be mindful of the importance of shame attenuation in facilitating and encouraging disclosure.